EVALUATION OF THE CENTER OF EXCELLENCE SMK PROGRAM IN IMPROVING THE ABSORPTION OF GRADUATES IN THE WORLD OF WORK AND INDUSTRY - Wuryanto, Joni; Supriyati, Yetti; Sutisna, Anan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The SMK Center of Excellence (SMK PK) program is a government initiative to improve the quality of vocational education to be more aligned with the needs of the world of work and industry. This study aims to evaluate the effectiveness of the SMK PK program in improving graduate absorption. The approach used in this research is mixed methods with a sequential exploratory design, which integrates qualitative and quantitative analysis. The evaluation was conducted using the CIPPO (Context, Input, Process, Product, Outcomes) and Kirkpatrick models to analyze the policy, resources, implementation, and impact of the program on graduates and industry. However, in this discussion, the analysis is focused on the Kirkpatrick model with a quantitative approach using multiple linear regression. The research sample was selected using purposive sampling technique, while the quantitative data analysis aims to measure the influence of the main factors in the success of this program. The results show that the availability of resources has a positive and significant influence on the quality of graduates, while the quality of teaching shows a significant negative influence. This indicates that improving the availability of resources, such as facilities and teaching materials, contributes more to improving the quality of graduates than the quality of teaching, which in the context of this study shows a negative relationship. In addition, the mediating variable does not have a significant role in bridging the relationship between teaching quality and resource availability to graduate quality.